Peran Administrasi dan Pelayanan dalam Mendukung Operasional Travel Umrah di PT. Safarindo Albarokah Umrah (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the role of administration and service in supporting the operational performance of PT. Safarindo Albarokah Umrah and to identify the challenges encountered as well as the strategies implemented to improve operational quality. The research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that administration plays a crucial role in managing pilgrims’ documents, recording payments, preparing departure schedules, and coordinating interdepartmental activities. Service supports operations by providing information, guidance, manasik training, and assistance throughout the departure process and the pilgrimage in Saudi Arabia. The synergy between administration and service enhances operational effectiveness, minimizes administrative errors, and increases pilgrims’ satisfaction and trust. The main challenges include incomplete documentation, regulatory changes, and the diverse characteristics of pilgrims, requiring continuous staff development, information technology utilization, and regular service evaluation.